Shifts in the Brussels-Capital Region electorate between the June 2009 regional elections and the 13 June 2010 federal elections - Pascal Delwit; Marjorie Gassner; Jean-Benoit Pilet; Emilie van Haute (Brussels Studies)
In the Brussels political area, the 13 June 2010 federal elections did not bring about shifts in the electorate which were as spectacular as those seen in Flanders or Wallonia if we refer to the 2007 elections. Significant changes may nevertheless be seen, in particular the progress made by the Socialist Party and the Reform Movement’s loss of ground during the elections. It is nevertheless interesting, in the timing of political and electoral life, to turn to the last elections – the 2009 Brussels regional elections – in order to analyse the shifts which occurred in the Brussels spectrum in the “short” period of political life, punctuated by events and changes which affect – sometimes quickly – the perceptions and the representations of parties and political life. The shifts which took place between the 2009 regional elections and the 2010 federal elections are analysed in this article. The work is based on an exit poll organised by the Centre d’étude de la vie politique (CEVIPOL) at Université libre de Bruxelles (ULB), with 3 000 inhabitants of Brussels.